2022
DOI: 10.3389/fpubh.2022.896087
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Chinese College Student Offspring's Physical Activity and Father Physical Activity During COVID-19 Pandemic

Abstract: The purpose of this study was to evaluate the relationship between the physical activity of Chinese college students and the physical activity of their parents. This relationship was examined by linear regression. The results showed that (1) the physical activities of China's college students will be refurbished and used for the parents. The offspring of COVID-19's later generation sports population showed that the offspring's physical activity was not broken during the later stage of the epidemic, and the coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Research conducted by Laiou et al ( 37 ) in an adult population concluded that the practice of any type of physical activity helps promote socialization among people. Similarly, Zhang et al ( 38 ) found that being physically active helps to have a better social image as well as increase the degree of socialization among peers. Regarding the type of physical activity, it has been found that low-intensity sports practice allows a higher degree of interaction among peers ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Research conducted by Laiou et al ( 37 ) in an adult population concluded that the practice of any type of physical activity helps promote socialization among people. Similarly, Zhang et al ( 38 ) found that being physically active helps to have a better social image as well as increase the degree of socialization among peers. Regarding the type of physical activity, it has been found that low-intensity sports practice allows a higher degree of interaction among peers ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Zhang et al ( 38 ) found that being physically active helps to have a better social image as well as increase the degree of socialization among peers. Regarding the type of physical activity, it has been found that low-intensity sports practice allows a higher degree of interaction among peers ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 91%
“…Relevant studies have shown that appropriate physical exercise can effectively alleviate state anxiety [11] and reduce depression [12,13]. During the normalization of the epidemic, the awareness of physical education among college students under closed management was strengthened, and the motivation and initiative to participate in physical exercise were increased to some extent [14]. Many studies have shown that moderate-intensity physical activity can effectively improve adverse states, such as depression and anxiety, and curb negative emotions among school students; the more active the level of physical activity commitment, the less negative emotions appear [15,16].…”
Section: Ofmentioning
confidence: 99%
“…In addition, because it is unregulated, social media can provide misinformation, which can easily lead to ambiguity and misunderstandings regarding COVID-19 and even to panic and confusion ( 12 ). Studies have shown that college students' KAP level and mental health are affected by stressful events during the COVID-19 pandemic ( 13 , 14 ), and the risk of anxiety, depression and other negative emotions among students increases, resulting in increased pressure ( 15 17 ). Therefore, good COVID-19-related knowledge, positive attitudes, healthy behaviors and good mental health are essential to effectively prevent and control pandemics and reduce the panic they cause ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%